Images of Books in Fyodor Dostoevsky’s Novel The Idiot. Review of the Collective Monograph: Kasatkina, Tatiana A., Corbella, Caterina, Magaril-Il’iaeva, Tatiana G., and Nikolay N. Podosokorsky. Books in the Book. The Role and Image of Books in Fyodor Dostoevsky’s Novel The Idiot. Ed. T.A. Kasatkina. Moscow, IWL RAS Publ., 2024. 392 p - Valentina V. Borisova (Достоевский и мировая культура: Филологический журнал)
The review examines the collective monograph by Tatiana Kasatkina, Caterina Corbella, Tatiana Magaril-Il’iaeva, and Nikolay Podosokorsky titled Books in the Book. The Role and Image of Books in Fyodor Dostoevsky’s Novel The Idiot (Ed. T.A. Kasatkina. Moscow, IWL RAS, 2024. 392 p.). The work reviewed represents a perspective of research that has actively developed in recent years, characterized by a new terminological thesaurus and a new methodology for studying the role and image of books-within-books, which is fundamentally different from the traditional intertextual approach. The authors’ primary focus in the monograph is on an analytical and synthetic study of all the books present in the novel The Idiot — including fiction, historical, memoir and sacred texts. As the IWL RAS scholars show, all these works are actualized both as objects and texts at the levels of poetics, ethics, aesthetics, and metaphysics. The review examines the various sections of the monograph and offers both positive and critical evaluations of the results and prospects of the research.